PEMILIHAN KUALITAS BIJI KOPI YANG TEPAT DALAM MENINGKATKAN USAHA BISNIS KOPI DENGAN MENGGUNAKAN METODE RETINEX DAN LOGIKA FUZZY - firdaus firdaus (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Coffee is a drink that has a high taste, not only used as a commodity but now coffee has become a way of life because the greater the demand for coffee by consumers, the greater the demand for the quality of the coffee produced. therefore the standard of coffee processing in various places is currently of great concern, starting from the planting process to the brewing stage. shape, color and other characteristics as for the research conducted, image processing was carried out first, the image obtained was an image taken using a webcamera from coffee beans to be selected after taking pictures of coffee beans, then image processing was carried out using the retinex method whereby In this method, the image quality improvement process will be carried out by explaining the quality of the image, and after the image processing is carried out, information about the image that has been processed will be obtained, then the analysis process will be carried out using the logic f method. uzzy in this method will analyze whether the beans have good characteristics based on the information obtained from the image if in the analysis process good results are obtained then the good coffee beans will be used to be processed and served to consumers but coffee that is of poor quality will not will be used to maintain the quality of coffee. As for all the processes and stages of information processing are carried out using Matlab because Matlab has a function that makes it easy to carry out all the stages and processes.